Analisa Kekasaran Permukaan Baja ST 37 Hasil Proses Milling Vertikal Akibat Variasi Proses Permesinan dan Media Pendingin - Cahyono, Hiding; Syuhri, Ahmad; Setiawan, Deny (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2024)
Minimum surface roughness in the machining process affects the quality of a material. Likewise with the results of the Vertical Milling process. One of the things that influences surface roughness in the milling process is the selection of machining parameters. Apart from selecting machining process parameters, another thing that influences surface roughness is the presence of coolant. The aim of this research is to determine the surface roughness results of ST37 steel due to variations in cutting speed, feed speed and coolant discharge during the vertical milling process. Data testing uses multiple linear regression. The research results show that the influence of the feeding speed parameter has the greatest influence and the smallest influence is on the coolant discharge, where the results of the regression test results are Ra = 100.636 *(v)-0.577 *(vf)0.159 *(q)-0.245 with a value R Square is 0.846 or 84.6%.